An Internal Replication Examining the Role of Issue Involvement, Relevance, and Additional Requirements to Maintain an Established Freedom among Older Adults. (14th October 2019) - Al-Ghaithi, Salah H; Reynolds-Tylus, Tobias; Quick, Brian L; Gonzalez, Andrea Martinez; Nead, Kaitlyn E
Abstract: The current research aimed to advance the psychological reactance theory literature by extending this framework to older adults (N = 525) age 55 or older. In doing so, this project tests two principles of reactance theory as well as exploring the relationship between reactance and a behavioral outcome. Results demonstrated that the threat of additional driver's license requirements, issue involvement, and the personal relevance of the threatened freedom increased freedom threat perceptions. In turn, freedom threat perceptions were positively associated with reactance. Reactance was positively associated with agreeing to sign a petition protesting the proposed requirements. The same pattern of findings was replicated within the context of maintaining low cost health insurance premiums. In addition to these main effects, two interactions (additional test requirements * issue involvement and additional test requirements * personal 2 relevance) were explored. Results are discussed with an emphasis on the theoretical and practical implications for psychological reactance theory among older adults.